Stable sorghum grain quality QTL were identified using SC35 × RTx430 mapping population. Issue 3 (26th July 2022) - Ayalew, Habtamu; Peiris, Shantha; Chiluwal, Anuj; Kumar, Ritesh; Tiwari, Manish; Ostmeyer, Troy; Bean, Scott; Jagadish, S. V. Krishna
Abstract: Understanding the genetic control and inheritance of grain quality traits is instrumental in facilitating end‐use quality improvement. This study was conducted to identify and map quantitative trait loci (QTL) controlling protein, starch, and amylose content in grain sorghum [ Sorghum bicolor (L.) Moench] grown under variable environmental conditions. A recombinant inbred line (RIL) population derived from a cross between RTx430 and SC35 was evaluated in six environments across Hays and Manhattan, KS. Significant variation was observed in genotype, environment, and genotype × environment interaction for all three quality traits. Unlike the RILs, the two parental lines did not show significant differences for these traits. However, significant transgressive segregation was observed for all traits resulting in phenotypic performance extending beyond the two parents. A total of seven protein, 10 starch, and 10 amylose content QTL were identified. Chromosomal regions and phenotypic variation (PVE) of QTL were variable across growing conditions. Quantitative trait loci hotspots for all three traits were detected on chromosomes 1 (115.2–119.2 cM) and 2 (118.2–127.4 cM). Candidate gene analysis indicated that these QTL hotspots were conditioned by several transcription factors, such as Cytochrome P450 and basic helix–loop–helix DNA binding protein, which regulate starch and protein accumulation in the grain. The identified genomic regions and underlying candidate genes provide a starting point for further validation and marker‐assisted gene pyramiding to improve sorghum grain quality. Core Ideas: Stable QTL controlling protein, starch, and amylose content were identified through multiple‐environment testing. Genomic regions conditioning multiple grain quality traits were identified on chromosomes 1 and 2. Grain quality QTL were conditioned by transcription factors that regulate starch and protein accumulation. NIR spectroscopy enables accurate prediction of grain quality traits in grain sorghum.